(untitled) (Medico Legal Update, 2021)
Background: In early pregnancy, it is essential to emphasize viability, and gestational age precisely. Researchers have tried to discover some useful sonographic indicators in early pregnancy so as to expect the outcome of the ongoing pregnancy. The aim of this study is to assess first-trimester ultrasound measurements for the prediction of early pregnancy loss. Subjects and Method: A prospective observational cohort study done in Tikrit city in outpatient clinic of obstetrics and gynecology department in Salah Al-Deen General Hospital from 1st February-31st August 2020. A random sample of 78 pregnant women selected, 8 were lost to follow up. The data collection done through a designed questionnaire, physical examination and transvaginal sonography assessment. Sonography assessment of the crown rump length (CRL), yolk sac (YS) and gestational sac (GS) diameters, & fetal heart rate (FHR) are recording. Results: Seventy pregnant women examined by using transvaginal ultrasonography at 6th,9th and 12th week of gestation. The readings at 6th week of gestation for the (GSD, YSD, CRL, and FHR) were (14.5±1.3), (3.2±1.8), (3.1±0.8), & (105±10.6) respectively, lower among those with first trimester loss than those continue pregnancy (26.1±5.2), (3.9±0.3), (5.1±0.5), and (119±3). The readings at 12th week of gestation for the (GSD, YSD, CRL, and FHR) were as follows; [(25.1±3.5), (3.6±0.3), (13± 2.1). & (165± 1)] were lower among with first trimester loss group than those continue pregnancy [(59.2±4.1), (4.5±0.7), (50.7±5.7) & (171±5)]. Conclusions: The current study found that lower GSD, YSD, CRL, and FHR may indicate early pregnancy loss.